2018
DOI: 10.2196/resprot.9916
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Aid Use in Older Adults With Postlingual Sensorineural Hearing Loss: Protocol for a Prospective Cohort Study

Abstract: BackgroundOlder adults with postlingual sensorineural hearing loss (SNHL) exhibit a poor prognosis that not only includes impaired auditory function but also rapid cognitive decline, especially speech-related cognition, in addition to psychosocial dysfunction and an increased risk of dementia. Consistent with this prognosis, individuals with SNHL exhibit global atrophic brain alteration as well as altered neural function and regional brain organization within the cortical substrates that underlie auditory and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
7
0
1
Order By: Relevance
“…Given the limitations of this study, including the small sample size, the magnitude of the effects reported here should not be interpreted as would be the case for a fully powered trial 36. Our baseline results have provided the motivation needed to proceed with a full-scale, randomized hearing loss intervention and a longer neuroimaging study with cognitive outcomes measured in the short term as well as after several years hearing aid use is needed 37. This may be the first prospective cohort randomized controlled trial to test the neural, cognitive and psychosocial efficacy of hearing aid use in adults with post-lingual SNHL.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Given the limitations of this study, including the small sample size, the magnitude of the effects reported here should not be interpreted as would be the case for a fully powered trial 36. Our baseline results have provided the motivation needed to proceed with a full-scale, randomized hearing loss intervention and a longer neuroimaging study with cognitive outcomes measured in the short term as well as after several years hearing aid use is needed 37. This may be the first prospective cohort randomized controlled trial to test the neural, cognitive and psychosocial efficacy of hearing aid use in adults with post-lingual SNHL.…”
Section: Resultsmentioning
confidence: 95%
“…In view of the problems encountered with the extraction of logged hearing aid use data in this pilot study, future studies will ensure that participants are instructed to manually record hours of hearing aid use every week, in order to confirm the automatically logged hearing use records. It is also hoped that our planned hearing loss intervention study, which will investigate the long-term impact of hearing aids on cognitive function,37 will address a further limitation of this pilot study.…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have grappled with these issues, and prospective studies of hearing interventions for long-term cognitive outcomes are planned or under way [ 24 – 27 ]. However, the limitations of conducting well-controlled hearing intervention studies with long-term cognitive outcomes means that the primary source of evidence will come from studies other than randomised controlled trials.…”
mentioning
confidence: 99%
“…Awareness has increased over the past decade regarding how the brain remodels itself in response to hearing impairment and the mechanisms underlying the processing and integration of auditory information; this increasing awareness is due to the development and advancement of neuroimaging technologies in auditory research, such as magnetoencephalography and functional magnetic resonance imaging (fMRI) ( Burton et al, 2012 ; Hughes et al, 2018 ). The complex processes of auditory information recognition and functional coding undergo restructuring in response to hearing impairment ( Andoh et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%